Peningkatan Peran Serta dan Dukungan Guru Melalui Pelatihan tentang PHBS sebagai Salah Satu Strategi Keberhasilan Pelaksanaan UKS PAUD di PAUD Wilayah Desa Wedomartani Sleman Yogyakarta - Fitriana, Lala Budi; Sukismanto, Sukismanto (Jurnal Pengabdian Dharma Bakti, 2019)
The UKs PAUD program is an integrated cross-program and cross-sectoral effort in order to improve health status as well as establishing clean and healthy life behavior of early childhood children. UKS is implemented in three main programs (TRIAS UKS) which includes health education, health services, and healthy school environment where if TRIAS UKS is implemented optimally it can improve health status and reduce morbidity in learners. This activities to improve teachers' knowledge about PHBS as one of the strategies of achieving the success of UKS PAUD. Training in PAUD teachers is conducted by lecture and health question and answer related to PHBS with power point and LCD media for 90 minutes. The result of the level of knowledge of early childhood teachers on PHBS prior to training is largely high ie 72%, the level of knowledge of early childhood teachers on PHBS after being given training is mostly high ie 90%. There is an increase in knowledge of early childhood teachers after training on PHBSKeywords: Teacher, Early Childhood, PHBS